ANALYSIS OF SECURITY RISKS BASED ON THE INFORMATION PROVIDED IN THE GENERAL DECLARATION OF ARRIVAL IN THE EUROPEAN UNION - POPEL, Sergii; YAKOVENKO, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The purpose of the article is to study the experience of European countries regarding the peculiarities of security risk analysis based on the information provided in the general declaration of arrival and to develop proposals for bringing domestic customs legislation closer to the legislation of the European Union. The article analyzes the features of security risk analysis based on the information provided in the general declaration of arrival in the European Union. The regulatory and legal bases for the use of the general declaration of arrival in European countries have been determined. The parties responsible for submitting preliminary data to the customs authorities, the deadlines for submitting the general declaration of arrival and the amount of data that must be submitted to the customs authority, depending on the type of transport on which the goods will be imported into the customs territory of the EU, were found. It was found that the data are specified in the general declaration arrival, the so-called "security notices", which are submitted to border customs before the import of goods into the customs territory of the European Union, enable customs authorities to carry out a risk analysis, primarily with the aim of determining the degree of security and the appropriate way of conducting customs control. Studied the procedure for assessing security risks based on the information submitted in the general declaration of arrival in the European Union and was differences with a similar procedure in Ukraine were found. Analyzed the actions of the customs authorities regarding the analysis of security risks based on the information submitted in the general declaration of arrival, actions in the event of changes to the previous notification, cases in which: submission of additional information may be required, a ban on the loading of goods